Digital human modeling : applications in health, safety, ergonomics, and risk management : 7th International Conference, DHM 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016, Proceedings /: applications in health, safety, ergonomics, and risk management : 7th International Conference, DHM 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016, Proceedings. (2016) - Unknown
No abstract available